2007
DOI: 10.1021/jo0708902
|View full text |Cite
|
Sign up to set email alerts
|

The Substituent Effect of the Methyl Group. Carbon 1s Ionization Energies, Proton Affinities, and Reactivities of the Methylbenzenes

Abstract: High-resolution carbon 1s photoelectron spectra have been measured for methyl-substituted benzenes. By using these data together with molecular structure calculations to predict the vibrational profiles expected in the spectra, it has been possible for the first time to assign 1s ionization energies to each of the inequivalent carbon atoms in these molecules. There exist linear correlations between the ionization energies and the energy changes for other chemical processes, such as enthalpies of protonation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 32 publications
7
57
0
Order By: Relevance
“…For 1,3-butadiene and 1,3-pentadiene we have shown that, in keeping with this expectation, there are such linear correlations between the carbon 1s ionization energies and the activation energies for addition of HCl at various positions in the molecule and between the carbon 1s ionization energies and the enthalpies of protonation. 4 The studies of the fluoro-and methyl-substituted benzenes 1,2,3 show similar linear correlations, but in some cases there are significant deviations of the data from a single correlation line. In particular, for the correlations between carbon 1s ionization energies and enthalpies of protonation there are four separate but nearly parallel lines for compounds that have 0, 1, 2, or 3 fluorine substituents that are either ortho or para to the site of ionization/protonation.…”
Section: Goals Accomplishments and Activitiesmentioning
confidence: 89%
See 2 more Smart Citations
“…For 1,3-butadiene and 1,3-pentadiene we have shown that, in keeping with this expectation, there are such linear correlations between the carbon 1s ionization energies and the activation energies for addition of HCl at various positions in the molecule and between the carbon 1s ionization energies and the enthalpies of protonation. 4 The studies of the fluoro-and methyl-substituted benzenes 1,2,3 show similar linear correlations, but in some cases there are significant deviations of the data from a single correlation line. In particular, for the correlations between carbon 1s ionization energies and enthalpies of protonation there are four separate but nearly parallel lines for compounds that have 0, 1, 2, or 3 fluorine substituents that are either ortho or para to the site of ionization/protonation.…”
Section: Goals Accomplishments and Activitiesmentioning
confidence: 89%
“…Two papers have been published and one submitted concerning substituent effects in substituted benzenes. The first of these has dealt with fluorine as a substituent, 1 the second with the methyl group as a substituent, 2 and the third on the combined effects of both fluorine and the methyl group. 3 In these papers we have shown that the effects of multiple substituents on not only carbon 1s ionization energies, but also reactivities and enthalpies of protonation, can be accounted for primarily by a linear additivity model.…”
Section: Goals Accomplishments and Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Atom ical approach that can reproduce the adiabatic and vertical C1s ionization energies of the molecules, observed [16][17][18][19][20][21] with the new generation synchrotrons, as accurately as possible.…”
Section: Moleculementioning
confidence: 99%
“…Recently, accurately observed values of adiabatic and vertical C1s ionization energies of alkanes [16], alkenes [17], alkynes [18], fluorobenzenes [19], methylbenzenes [20], and fluoromethylbenzenes [21] have been published. All the experimental values were measured using new generation synchrotorons.…”
Section: Introductionmentioning
confidence: 99%